The psychological impact of agency worker utilisation. Issue 6 (30th September 2014) - Toms, Simon; Biggs, David
Abstract : Purpose: – Agency work represents a unique form of employment that has received increased attention in recent years. Supporters of the agency employment industry have cited increased accessibility and flexibility at an individual and organisational level, yet critics have highlighted disparities in treatment and the limited protection afforded by the contract. Previous psychological studies into the working experiences of these employees have forwarded a series of findings that have frequently conflicted, so this paper begins by exploring research into the areas of motive, job satisfaction, job security, and organisational support. The purpose of this paper is to better understand how this form of employment can psychologically affect agency workers by focusing upon these key areas. Design/methodology/approach: – The study's research design incorporated 25 semi-structured interviews with agency workers, recruitment consultants, and representatives from third-party employers. These interviews were then supplemented by longitudinal data from follow-up interviews conducted with agency workers from the initial sample. During the study, the researcher undertook a number of agency working assignments, and ethnographic analysis of diary extracts represented a third source of data. Findings: – Results highlighted the importance of motive, as it was found to influence how agency workers viewed their employment. The lack of obligation in temporary contracts was perceived to lead to isolation from permanent colleagues, increase vulnerability, and reduce job security and organisational commitment. Research limitations/implications: – Findings strongly supported the claim that the pre-assignment motives of individuals had a significant impact upon their resulting experiences. Agency workers employed in longer-term assignments reported greater integration into the organisation, resulting in increased commitment towards the third-party employer, and improved relationships with permanent staff. Originality/value: – The current research incorporated multiple perspectives to create an increased understanding of the agency employment industry and its impact upon individuals.